Coal Temperature Variation Mechanism during Gas Desorption Process - T. Yang; B. S. Nie; Q. S. Ye; P. Chen (Advances in Civil Engineering)
To further reveal the mechanism of coal gas migration, the reasons for coal temperature changes during the methane desorption process were analyzed from the aspect of molecular motion and the thermodynamic theory. The temperature change mechanism was investigated, and the mathematical equation was established to describe the variation of temperature change during the methane desorption and diffusion process. The established equation was applied for the calculation of temperature change for two types of coal samples, and the measured and theoretical values of temperature changes were obtained. The results show that the temperature changes in the coal gas desorption process are mainly caused by the heat adsorption. The heat adsorption phenomenon was also caused by free gas expansion during the pressure relief process. The gas diffusion and work done for gas seepage also need heat adsorption. The temperature change is positively correlated to the coal gas pressure, quantity, and limit value of gas desorption volume. Due to the poor insulation in the test system, the difference between the theoretical and the measured temperature change values increase with the adsorption equilibrium pressure. It is helpful to further reveal the mechanism of coal and gas outburst. It also has an important reference value for controlling gas dynamic disasters in coal mines.